Cell differentiation and osseointegration influenced by nanoscale anodized titanium surfaces. (July 2012) - Lavenus, Sandrine; Trichet, Valérie; Le Chevalier, Sébastien; Hoornaert, Alain; Louarn, Guy; Layrolle, Pierre
Aims: We aimed to study the interactions between human mesenchymal stem cells and the bone integration of nanostructured titanium implants.Materials & methods: Nanopores of 20, 30 and 50 nm were prepared by anodization of titanium at 5, 10 and 20 V in a mixture of fluorhydric and acetic acid. Ti 30 and 50 nanostructures promoted early osteoblastic gene differentiation of the human mesenchymal stem cells without osteogenic supplements. The osseointegration of nanostructured and control titanium implants was compared by implantation in rat tibias for 1 and 3 weeks.Results: The nanostructures significantly accelerated bone apposition and bone bonding strength in vivo in correlation with in vitro results.Conclusion: These findings demonstrate that specific nanostructures controlled the differentiation of cells and, thus, the integration of implants in tissues. These nanoporous titanium surfaces may be of considerable interest for dental and orthopedic implants. Original submitted 10 September 2011; Revised submitted 11 November 2011; Published online 6 March 2012